2020
DOI: 10.1021/acs.jafc.9b06248
|View full text |Cite
|
Sign up to set email alerts
|

Amylopectin-Sodium Palmitate Complexes as Sustainable Nanohydrogels with Tunable Size and Fractal Dimensions

Abstract: Starch-based nanohydrogels with polyelectrolyte characteristics may find unique applications. Herein, the branch chains of amylopectin (AP) were elongated to different extents by amylosucrase, followed by complexation with sodium palmitate (SP) to produce nanohydrogels. Modified AP (mAP) with a longer chain length displayed a better ability to complex with SP, and the mixtures exhibited nanosized particles with an average diameter ranging from 153.5 to 1049.8 nm. The gel strength of bulk nanohydrogels was depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The microstructure of cooked rice flour can be resolved by rheological test. , For all samples, both storage modulus ( G ′) and loss modulus G ″ increased with the increase of ω, and the magnitude of G ′ was higher than that of G ″ at the range of frequency examined (Figure ). G ′ and G ″ indicate the elastic and viscous properties, respectively, and thus the cooked rice flour had a weak-gel behavior . The data of log G ′ and log G ″ versus log ω were subjected to linear regression as follows: log G = K + n log ω log G = K + n log ω …”
Section: Resultsmentioning
confidence: 99%
“…The microstructure of cooked rice flour can be resolved by rheological test. , For all samples, both storage modulus ( G ′) and loss modulus G ″ increased with the increase of ω, and the magnitude of G ′ was higher than that of G ″ at the range of frequency examined (Figure ). G ′ and G ″ indicate the elastic and viscous properties, respectively, and thus the cooked rice flour had a weak-gel behavior . The data of log G ′ and log G ″ versus log ω were subjected to linear regression as follows: log G = K + n log ω log G = K + n log ω …”
Section: Resultsmentioning
confidence: 99%
“…Dynamic modulus can be used to examine the interactions between the disperse phase and the continuous phase in some polymer solutions [21]. In general, G' represen the energy stored as mechanical energy, whereas G" measures the energy dissipated heat, and mostly represents the viscous portion [29]. As shown in Figure 3A,B, the G' an G" of all samples increased as the scanning frequency increased from 0.1 Hz to 10 H Moreover, the value of G' was slightly higher than that of G", indicating that both WR and the WRS-PEC blends had weak gel properties.…”
Section: Dynamic Rheological Propertiesmentioning
confidence: 99%
“…The formation of starch gels involves the reassociation of starch chains, where the hydrogen bonding formed between adjacent starch chains determines the gel strength. According to previous studies [ 22 , 28 ], the addition of sodium palmitate decreased the viscosity of the amylose solution, and no visual or microscopic evidence of retrogradation was observed for amylose because the electrostatic repulsion restricted the amylose reassociation. In this study, the hydrophobic forces transferred the hydrophobic chain of PS into the amylose helix cavity, and the ionization of −COOK provided the polyelectrolyte characteristics of HAS-PS ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 87%
“…Additionally, the magnitude of the negative ζ potential of HAS-PS dispersions gradually increased from −22.2 mV to −32.8 mV when the addition of PS increased from 0.5 mM to 2.0 mM ( Figure 1 ). In a previous study [ 22 ], the starch-lipid complexes prepared from chain-elongated amylopectin and sodium palmitate also showed polyelectrolyte characteristics, and structural analysis revealed that the hydrophobic hydrocarbon chain of sodium palmitate is trapped in the starch particles via a V-type helix formation, and the carboxylate group was present on the particle surface. Consequently, a higher magnitude of ζ potential might result from a greater inclusion of PS within the HAS-PS particles.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation